Irma Stern (1894-1966) : the creation of an artist's reputation in her lifetime and posthumously, 1920-2013 - Sinisi, Sarah (Michaelis School of Fine Art, 2016)
This dissertation examines the reception of the artist, Irma Stern, from 1920 until 2013. Irma Stern has, since her lifetime, been one of South Africa's most celebrated artists. She has received a great deal of scholarly attention, attention in the popular press and on-going recognition in the market place. Through an evaluation of press clippings, literature, archival material (photographs, the minutes of meetings and letters) and market results, this study questions how Stern has come to assume such a privileged position, why she is of such scholarly interest and how she is valued in the market. The impact of different variables on Stern's reception - including social, political and intellectual factors - is investigated. It is proposed that, initially, the artist actively promoted herself, thus playing an important role in establishing her fame. However, her reputation has been built over time and what emerges as important is that audiences have approached and interpreted Stern differently at different times. During the artist's lifetime she was admired for her perceived ability to capture the 'spirit of Africa', apparently evident in her paintings of those culturally different from her. These paintings - of black African, Indian, coloured and Arab subjects - have remained an integral aspect of the artist's reputation and they are at the centre of much of the scholarly debate on the artist in the 1990s and 2000s. Stern has provided rich material for writers at different times and of different ideological positions - from colonial to postcolonial discourse and feminist studies. Also relevant to Stern's sustained reputation is the international recognition the artist has received. Stern's links to German Expressionism and recognition from foreign scholars and institutions served to legitimate the artist to a South African audience in her lifetime and posthumously. Moreover, the market has had an impact on Stern's reputation. While she was commercially successful in her lifetime, in the early 2000s her market values exceeded those of earlier periods and surpassed those of other twentieth-century South African artists. As a result, Stern's reputation in the 2000s is linked to her high market values; this dissertation closely investigates some of the factors that have influenced this market value. In conclusion, this dissertation fills a gap in the literature because it 1) analyses the artist's market and 2) provides an in-depth investigation of the development of the artist's reputation. A study in reception, it does not add to the already plentiful appraisals of the artist's work but considers instead how this work has fared within the context of the academic, popular and commercial art world.